Health and care in neoliberal times - Small, Neil (Milton Park, Abingdon, Oxon ; New York : Routledge, 2023)
"This book argues that neoliberal changes in health and social care go beyond resource allocations, priority setting, and privatisation, and manifest in an invidious erosion of the quality of our social relationships, including relationships between care provider and care recipient. Exploring the interaction of politics, economics and social change and their impact on healthcare and the wider welfare state, this is an important contribution for students and researchers in health and social care, sociology, political science and management studies"--
The Nature of Change -- Change in Action. Neoliberalism and the economics of the NHS -- Changing organisations and the impact of neoliberalism on health professions -- Consequences: how neoliberalism makes us sick -- How ideological shifts are manifest in society : in collective social attitudes and in individuals -- Culture -- Aspects of culture that might be damaged and need repair.
OCLC-licensed vendor bibliographic record.
Keywords: Medical policy -- Great Britain; Medical care -- Political aspects -- Great Britain; MEDICAL / Hospital Administration & Care